Rare Variants of Ependymoma: A Report of Four Cases and a Review of the Literature - Murad A. Alturkustani (Journal of King Abdulaziz University: Medical Sciences, 2023)
Ependymomas are brain tumors that have a wide spectrum of morphological patterns. Rare or unusual patterns of ependymoma can resemble other neoplasms and result in erroneous diagnosis, and management. Four out of 22 ependymoma cases in the pathology archive of King Abdulaziz University Hospital in the last decade had these patterns. The fi rst case was of ependymoma with multinodular growth and diff erent types of ependymal diff erentiation, including subependymoma, classic ependymoma, and astroblastoma. Dysplastic neurons were associated with the neoplastic growth. This combination can be interpreted as ganglioglioma (i.e., with ependymoma representing the glial component, World Health Organization grade I) or alternatively as ependymoma with dysplastic neurons (World Health Organization grade II). The second case was of a rare variant of intracranial extra-axial ependymoma with lobular and papillary architecture. The third case was of a previously unreported combination of clear cell and giant cell ependymoma. The fourth case was of epithelioid ependymoma with fi brillary background and a peculiar arrangement of the tight clustered epithelioid cells. This report expands the morphological spectrum of ependymoma by introducing diff erent, previously unreported combinations of patterns that were observed in individual tumors, as well as rare locations and architectures.